Legal Protection of Land Control of Baduy Indigenous People and Sedulur Sikep - Utomo, Laksanto; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2017)
Applicability of UUPA, a step forward in the land law, but with the foundation of land tenure and the former western lands that are not owned by an individual into a state land "directly controlled by the State to the maximum benefit of the people", it becomes a big problem, what is it? Proof of ownership of land should be formal and based on the written evidence proved village government (Lurah), how to indigenous peoples who are not familiar with reading and writing, they are farmers working in the tradition to the next. In the Local Rules Samin people not give legal protection to ownership. Meanwhile the Lebak’s District Government issued Decree’s No. 32, 2001 About Protection of Land Rights Baduy society, to guarantee the continuity of the Baduy. This local regulation should be used as an example for legal protection against indigenous peoples.